Enhancing Reading Comprehension through the Cooperative Integrated Reading and Composition (CIRC) Strategy - Patty, Jusak (Research Horizon, 2023)
This study explores the transformative potential of the Cooperative Integrated Reading and Composition (CIRC) learning strategy in enhancing student engagement and learning outcomes. Through two carefully executed cycles, the study delves into the dynamic interplay between educators and students and its impact on the learning landscape. Drawing from constructivist principles, the CIRC strategy emphasizes collaborative discourse and active knowledge construction, fostering cognitive and affective growth. The research reveals a significant shift in student engagement, with average scores climbing from 3.37 to 4.12 across cycles, substantiating the strategy's efficacy in promoting meaningful learning experiences. Furthermore, applying the CIRC strategy demonstrated a notable increase in post-test scores, from 69.64 to 75.04, along with a rise in the proportion of students mastering the subject matter, from 60% to 80%. While the strategy boasts transformative potential, its implementation challenges include time investment and creating conducive group discussion environments. This study underscores the importance of dynamic learning approaches that empower students to actively construct knowledge and apply it in real-world contexts, reinforcing the role of educators in catalyzing this evolution. The CIRC strategy is powerful in bridging theory and practice, offering a holistic educational experience that resonates far beyond the classroom.